PWE-067 Variability in reporting and interpretation of calprotectin levels in the united kingdom. (22nd June 2015) - Brookes, MJ; French, J; Logan, R; Ford, C; Gama, R; Robins, A; Whitehead, S; Steed, H
Abstract : Introduction: Faecal calprotectin (f-Cp), a calcium binding protein, is a product of mucosal granulocyte infiltration in Inflammatory Bowel Disease (IBD). In 2013 NICE supported its use in the UK as a tool for distinguishing between IBS and IBD. However we have previously reported inter-assay variability which may limit the efficacy of this test in IBD and current practice in reporting f-Cp seems to vary across the UK. The aim of this questionnaire was to determine the variability in reporting of f-Cp results to clinicians from laboratories across the UK. Method: A questionnaire evaluation of all laboratories in the UK who currently perform a f-Cp assay and are members of the national quality assessment programme (UK NEQAS for Faecal Markers of Inflammation). Results: The questionnaire was sent to 59 laboratories in the UK and responses were received from 69% (n=41). All laboratories performed their own assay on site. The reference ranges varied between laboratories being <50 ug/g in 82.9% (n=34), <60 ug/g in 4.9% (n=2) and other ranges were used by the remainder of laboratories (12.2%; n=5). The reference range was either derived from the commercial supplier in 58.5% (n=24) or by the laboratory locally in 41.5% (n=17). An indeterminate range for f-Cp was provided by only 56.1% (n=23) of laboratories. The reporting of this indeterminate range was however very variable between sites, with the commonest reported range being 50-200 ug/g by 30.4% (n=7) of these laboratories. 70.7% (n=29) of laboratories generated a report which also provided clinical advice. For those laboratories who provided an indeterminate range, only 52.2% (n=12) also provided clinical advice on how to interpret these results. Conclusion: The normal or reference range for f-Cp across UK laboratories seems to be relatively standardised. However for results outside of the normal reference range there seems to be increasing variability, which is particularly highlighted by the wide practices with regards to interpreting indeterminate results. Disclosure of interest: None Declared.